PENGARUH PENGGUNAAN MEDIA JAM DINDING TERHADAP KEMAMPUAN LITERASI DAN NUMERASI - Crismono, Prima Cristi; Khumayroh, Fadilatul Nur (SIGMA, 2025)
The purpose of this study is to analyze the extent to which the use of wall clock media can improve the literacy skills of elementary school students, as well as to examine its impact on enhancing numeracy skills at the same educational level. This research employs a quantitative approach using a quasi-experimental design to measure the effect of wall clock media on students' literacy and numeracy abilities. The research methodology involves an experimental type with control and experimental group design. Based on the results, it can be concluded that the use of wall clock media has a significant positive impact on improving the literacy and numeracy skills of elementary school students. This medium has been proven to effectively enhance learning outcomes.